Budgetary bias in the Finnish public hospital system. Issue 4 (17th January 2020) - Karila, Alpo; Vakkuri, Jarmo; Lehto, Juhani
Abstract : Purpose: The purpose of this paper is to analyze the dynamics of budgetary biasing in the context of public hospitals. Design/methodology/approach: The study applies theories of accounting and budgeting behaviors in the specific institutional context of health care systems. Based on the theoretical framework, data from interviews with hospital budget officers were analyzed using qualitative content analysis. Findings: A typology of biases is provided. It proved to be useful and highlighted the central empirical assumptions and preliminary results of biasing dynamics. Practical implications: Understanding the logic of budgeting actors and the drivers of bias may help explain why bias so often appears in health care budgeting. It further contributes to understanding whether the bias is functional or dysfunctional. Originality/value: The concepts of budgetary bias are rarely used in the context of health care budgeting, so the study fills a gap in research knowledge.